Enhancing Preschoolers’ Online Learning through Digital Storybooks in Brunei Darussalam (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
In this 21st century, a digital storybook is one of the innovative educational strategies that may be used for online learning to engage preschool children in deep and meaningful learning. Research examining the use of digital storybooks for online learning found that it had a beneficial impact on preschool children’s learning attitudes. This research also looks at the level of learning engagement when the digital storybook is utilised for online learning. In addition, this research will investigate the challenges of employing a digital storybook for preschool children's online learning. This study used a qualitative research method to acquire the essential data for the research aims. Only four preschool children aged between 5 and 6 were chosen as research participants throughout two research cycles. The results indicated that employing a digital storybook for preschool children's online learning has changed their views toward learning, making it more enjoyable. This is because the digital storybook includes animation and sound. Furthermore, the study revealed that preschool children were more focused and attentive in their learning, allowing them to answer the questions about the lesson's content in the digital storybook without any assistance. Other than that, this research also revealed the difficulties when utilising digital storybooks for preschool children's online learning. Overall, the research has given insight into the use of digital storybooks for preschool children in Brunei Darussalam during the second wave of the COVID-19 pandemic.